Produksi Beta-Glukan dari Saccharomyces cerevisiae dan Aktivitas Antioksidan pada Sel Darah Merah yang Diinduksi t-BHP - KUSMIATI KUSMIATI; NI WAYAN S. AGUSTINI; SWASONO R. TAMAT; BAYU RIANTO (Fakultas Farmasi Universitas Pancasila, 2012)
Beta glucan is a polysaccharide that can be found in cereals, yeast, bacteria, and algae. Beta glucan produced by Saccharomyces cerevisiae has the ability to enhance the body’s defense system. The study aims to investigate the antioxidant activity of B glucan produced by three strains of Saccharomyces sp BR 1, BR 2,and SC. Antioxidant activity assay was carried out in vitro on t BHP induced red blood cells (REC) by observing the level of catalase activity, SOD activity and MDA levels as lipid peroxidation product. The investigation was performed on 6 groups: normal control, negative control, positive control (RBC+ t-BHP + vitamin E 100 IU), and samples (RBC+t-BHP) treated with 1.4 µg/mL β-glucan from Saccharomyces strain BR1, BR2 and SC respectively. Saccharomyces cerevisiae strain SC produced the highest β-glucan of 88.70% (glucose equivalent), while the BR1 and BR2 of 22.56% and 46.28% respectively. Antioxidant activity assay showed that the highest increase in catalase activity (581.48%) was given by the B glucan from SC strain, the highest increase of SOD activity and decrease of MDA levels were given by the β- glucan from BR1 strain (359.17% and 48.18%) as compared to negative controls. Statistical test (α = 0.05) showed antioxidant activity of β-glucan from Saccharomyces Sp BR2 and SC did not differ significantly from the activity of vitamin E (100 IU).